2014
DOI: 10.1177/1933719114525275
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Low Glycemic Index Diet in Pregnancy on Markers of Maternal and Fetal Metabolism and Inflammation

Abstract: This is a secondary analysis of 621 women in ROLO study, a randomized control trial of low glycemic index (GI) diet in pregnancy to prevent the recurrence of macrosomia, which aims to assess the effect of the diet on maternal and fetal insulin resistance, leptin, and markers of inflammation. In early pregnancy and at 28 weeks, serum was analyzed for insulin, leptin, tumor necrosis factor a (TNF-a), and interleukin 6 (IL-6). At delivery, cord blood concentrations of leptin, TNF-a, IL-6, and C-peptide were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…In a large dietary intervention study, women in the intervention group were advised to maintain a low glycaemic diet at on average 15 weeks of pregnancy [70]. This intervention was compared with usual care, and although women in the intervention group gained less weight, no effects were found on maternal glucose, insulin sensitivity or on cord blood insulin [71]. In a small intervention study, a diet enriched with docosahexaenoic acid (DHA, an omega-3 fatty acid) initiated in the second half of pregnancy led to lower cord blood insulin levels [72].…”
Section: How To Prevent the Fetal Changes In Maternal Diabesitymentioning
confidence: 99%
“…In a large dietary intervention study, women in the intervention group were advised to maintain a low glycaemic diet at on average 15 weeks of pregnancy [70]. This intervention was compared with usual care, and although women in the intervention group gained less weight, no effects were found on maternal glucose, insulin sensitivity or on cord blood insulin [71]. In a small intervention study, a diet enriched with docosahexaenoic acid (DHA, an omega-3 fatty acid) initiated in the second half of pregnancy led to lower cord blood insulin levels [72].…”
Section: How To Prevent the Fetal Changes In Maternal Diabesitymentioning
confidence: 99%
“…Insulin resistance level changes during gestation are not commonly measured as primary outcomes in previous LGI intervention trials. One study by Walsh et al conducted in a subgroup of low glycemic index diet in pregnancy to prevent macrosomia The Randomised cOntrol trial of Low (ROLO) study [28] reported some benefits of LGI diet consultations initiated from early gestation to maternal insulin resistance [29]. Participants in the LGI intervention group also gained less weight by 1.3 kg than those in the control group [28]; the effect size is similar to what we observed in our study (1.6 kg).…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the effects of prenatal dietary patterns associated with inflammation have reported mixed results. Neither a low glycemic index diet [ 95 ] nor an antihypertensive diet [ 96 ] among pregnant women exerted any effects on markers of inflammation, although a high-complex carbohydrate/low-fat prenatal diet was associated with lower expression of pro-inflammatory genes in adipose tissue [ 26 ]. The null findings with respect to inflammation in some of the aforementioned studies may be attributed to the characterization of diets, which may not necessarily address specific dietary components that have the potential to either induce or dampen an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%